Evaluación económica y ambiental de los desechos forestales producidos en los aserraderos de la región norte de la Provincia de Los Ríos. - Avilés Jama, Anthony Alfonso (2019)
The present investigation is carried out in the northern region of the province of Los Ríos, where three cantons are evaluated; Quevedo, Valencia and Buena Fe, which has the main objective of economic and environmental evaluation of food in the sawmills of the northern region of the province of Los Ríos. It was possible to evaluate a total of 48 elements of mechanical transformation and commercialization of wood. Deposits, sawmills, pallets, cabinets, car bodies and mixed. The three cantons were evaluated by means of surveys and in turn the quantities of wood that these establishments manage were estimated, the amount of waste they produce at the time of the transformation of the wood is estimated, and the solid waste is assessed economically. That produce each type of industries in the evaluated cantons. The canton that obtained the greatest volume of waste was the Canton Buena Fe with about 467.29 cubic meters of forest waste, generating not only waste in its production but also generating waste to the environment since these residues are mostly burned and another part are given to the communities that are dedicated to swine and poultry. By means of calculations carried out described in the methodology, it was possible to identify that the establishment that generates the greatest volume of forest waste is the establishments that manufacture pallets, since this product has a great demand in the commercial field, the industries that elaborate pallets must handle large quantities of volume per month and this generates solid waste that later use to burn in cauldrons and dry the wood they buy to make the new pallets, this burnt solid waste releases carbon dioxide into the air generating impact to the environment and the community that surrounds them.